Resistance to white spot syndrome virus in the European shore crab is associated with suppressed virion trafficking and heightened immune responses - Millard, Rebecca S.; Bickley, Lisa K.; Bateman, Kelly S.; Verbruggen, Bas; Farbos, Audrey; Lange, Anke; Moore, Karen A.; Stentiford, Grant D.; Tyler, Charles R.; van Aerle, Ronny; Santos, Eduarda M. (Frontiers in Immunology, 2022)
All decapod crustaceans are considered potentially susceptible to White Spot Syndrome Virus (WSSV) infection, but the degree of White Spot Disease (WSD) susceptibility varies widely between species. The European shore crab Carcinus maenas can be infected with the virus for long periods of time without signs of disease. Given the high mortality rate of susceptible species, the differential susceptibility of these resistant hosts offers an opportunity to investigate mechanisms of disease resistance. Here, the temporal transcriptional responses (mRNA and miRNA) of C. maenas following WSSV injection were analysed and compared to a previously published dataset for the highly WSSV susceptible Penaeus vannamei to identify key genes, processes and pathways contributing to increased WSD resistance. We show that, in contrast to P. vannamei, the transcriptional response during the first 2 days following WSSV injection in C. maenas is limited. During the later time points (7 days onwards), two groups of crabs were identified, a recalcitrant group where no replication of the virus occurred, and a group where significant viral replication occurred, with the transcriptional profiles of the latter group resembling those of WSSV-susceptible species. We identify key differences in the molecular responses of these groups to WSSV injection. We propose that increased WSD resistance in C. maenas may result from impaired WSSV endocytosis due to the inhibition of internal vesicle budding by dynamin-1, and a delay in movement to the nucleus caused by the downregulation of cytoskeletal transcripts required for WSSV cytoskeleton docking, during early stages of the infection. This response allows resistant hosts greater time to fine-tune immune responses associated with miRNA expression, apoptosis and the melanisation cascade to defend against, and clear, invading WSSV. These findings suggest that the initial stages of infection are key to resistance to WSSV in the crab and highlight possible pathways that could be targeted in farmed crustacean to enhance resistance to WSD.